ANALYSIS OF CONSUMER CHARACTERISTICS IN ONLINE FRUIT AND VEGETABLE PURCHASES IN THE DIGITAL ERA - Setiyani, Rahmawati; Waluyo, Sugeng Edi; Putra, Rajendra Agidya (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
The digital era provides various conveniences for society. Technological developments have touched various fields including the business sector and become an important part of business sustainability. One of the strategic steps taken by business actors is to conduct online sales. The agricultural sector is one sector that has been significantly impacted by technological advances. Fruit and vegetable products are one type of product offered through online shops. The purpose of this study is to determine the characteristics of consumers who purchase fruit and vegetable products online. The results of the analysis of consumer characteristics in purchasing fruit and vegetables online in the digital era are dominated by female consumers by gender as much as 63%. Consumers in purchasing fruit and vegetable products online by age are dominated by 20 to 30 years old as much as 53%. Consumers in purchasing fruit and vegetable products online are dominated by high school education levels as much as 57%. Consumers in purchasing fruit and vegetable products online by type of work vary, with a dominance of housewives, students and others as much as 49%. The characteristics of consumers in purchasing fruit and vegetable products online based on monthly income from the research results are dominated by those with incomes of less than Rp. 1,000,000,-. as much as 34%.